Peningkatan Dukungan Sosial Orang Tua dengan Anak Skizofrenia melalui Solution Focused Therapy - Peristianto, Sheilla Varadhila; Lestari, Sri (Jurnal Psikologi, 2018)
Intrusive parental behavior towards children with schizophrenia did not support an effort to prevent recurrence and achieve a good quality of life. This research was aimed to improve parental social support through Solution Focused Therapy in order to recover the quality of life for children with schizophrenia. Six parents who had a child with schizophrenia participated in this quasi-experimental research using a pretest-posttest control group design. The Social Support Scale which adapted from the Interpersonal Support Evaluation List was used to measure parental support. The participants were divided into an experimental and control group. The result of this research showed a difference in social support between the experimental and control group. Giving Solution Focus Therapy to parents can improve parental social support for children with schizophrenia. The improvement of parental social support was expected to preserve better quality life of children with schizophrenia in order to relapse prevention.